2019
DOI: 10.11606/s1518-8787.2019053001087
|View full text |Cite
|
Sign up to set email alerts
|

Maternal characteristics and type of prenatal care associated with peregrination before childbirth

Abstract: OBJECTIVE: To analyze the maternal characteristics and type of prenatal care associated with peregrination before childbirth among pregnant women in a northeastern Brazilian state. METHODS: Quantitative and transversal study, with descriptive and analytical approaches, part of the Nascer em Sergipe research held between June 2015 and April 2016. A total of 768 puerperal women proportionally distributed across all maternities of the state (n = 11) were evaluated. Data were collected in interviews and from prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
5
0
5
Order By: Relevance
“…These areas require strategic actions in order to reduce premature mortality. In health care planning, at different management levels (state, regional and local), the main gaps in maternal and child health care need to be considered, including deaths that may be prevented through healthcare actions (Mendes et al, 2019;Weiland et al, 2021). Strengthening and expanding the obstetrics and neonatology care network, prioritizing immediate low-cost actions, such as early prenatal care, would reduce the number of premature deaths (Al-Sheyab et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These areas require strategic actions in order to reduce premature mortality. In health care planning, at different management levels (state, regional and local), the main gaps in maternal and child health care need to be considered, including deaths that may be prevented through healthcare actions (Mendes et al, 2019;Weiland et al, 2021). Strengthening and expanding the obstetrics and neonatology care network, prioritizing immediate low-cost actions, such as early prenatal care, would reduce the number of premature deaths (Al-Sheyab et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de o Brasil apresentar boa cobertura de assistência pré-natal, a qualidade e a adequação ainda são insuficientes. (14) Estudo sobre qualidade pré-natal realizado, no Peru, identificou que quatro a cada dez mulheres não receberam assistência de qualidade. O número insuficiente de consultas e poucas orientações foram os principais problemas identificados.…”
Section: Discussionunclassified
“…Despite Law 11,634/2007 ensuring women have prior knowledge of the maternity hospital where they will give birth, pilgrimages still occur. A study with 768 women from Sergipe showed that 29.4% had an antepartum pilgrimage ( 4 ) . Furthermore, the Stork Network Strategy highlights the need to strengthen the Health Care Network guidelines and integrated regional planning, in order to guarantee access to health services ( 7 ) .…”
Section: Introductionmentioning
confidence: 99%